Diversifikasi roti sorgum lokal unggulan untuk menuju ketahanan pangan global nusantara yang sehat - Almayda Andriana Firmansyah (Institute for Advanced Science Social, and Sustainable Future, 2023)
Global food security has been tested over the last three years due to the COVID-19 pandemic, the Ukrainian war, and the economic recession. State food authorities must take strategic steps to overcome a potential food crisis that could have multifaceted impacts. Food diversification with sorghum can be one solution to overcome the potential global food crisis in Indonesia and the world. One of the diversified sorghum products that can be consumed globally is bread. This study aims to analyze the advantages of the idea of superior Indonesian sorghum bread made from local varieties of sorghum in terms of agriculture, global health, and international trade economics, along with presenting a global product commercialization strategy to build the sustainable benefits of Indonesian sorghum for global food security. The study in this writing used a qualitative paradigm with a rationalistic approach. The study results show that sorghum bread has a high potential demand as a nutritional requirement for global society. The development of Nusantara sorghum bread has 2 types of products: plain bread and sandwiches made from local sorghum. The aim of local sorghum as a means of food diversification on a global scale through the concept of Indonesian sorghum bread can bring new profits to the country's economy and open up new business opportunities for the community. However, it is not easy to transform consumer behavior by consuming new carbohydrates. Hence, the selection of ingredients, improving food quality and nutrition, and policy efforts to introduce local varieties of sorghum bread products must be carried out at the local level.